Immunoprotectivity of Valine–glycine repeat protein G, a potent mediator of pathogenicity, against Acinetobacter baumannii. (July 2021) - Pazoki, Mahdieh; Darvish Alipour Astaneh, Shakiba; Ramezanalizadeh, Fatemeh; Jahangiri, Abolfazl; Rasooli, Iraj
Highlights: VgrG, the core component of T6SS is a potent mediator of A. baumannii pathogenicity. Two conserved sequences of vgr G1159-2196 and vgr G1159-1502 were identified antigenic. vgrg 1159-1502 was implanted in Loopless C lobe of N. meningitidis for display. BALB/c mice were immunized with these proteins and challenged with A. baumannii . The conserved region of VgrG develops protection against A. baumannii infections. Abstract: Type VI Secretion System (T6SS) contributes to both virulence and antimicrobial resistance in Acinetobacter baumannii. Valine–glycine repeat protein G (VgrG) is the core component of T6SS that exists in many bacterial pathogens that have emerged as a potent mediator of pathogenicity in A. baumannii. Two conserved sequences of vgr G 1263-2295 and vgr G1263-1608 were identified antigenic in various strains of Acinetobacter baumannii . The vgrg 1263-1608 sequence was implanted in the Loopless C lobe (LCL) from N. meningitidis for surface display and exposure to functional epitopes. The VgrG and LCL-VgrG were expressed and purified. Groups of BALB/c mice were immunized with these proteins and challenged with A. baumannii . Specific IgG titers, whole-cell ELISA, animal survival rates in active and passive immunizations, the bacterial burden in mice tissues, and cytotoxicity of the proteins were determined. The specific IgG suppressed bacterial burdens in the organs, and increased survival rates were noted in the immunized mice. LCL-VgrG immunization provided better protection against A. baumannii infection than the VgrG immunization. The conserved region of VgrG is probably a safe immunogen to effective vaccine development or an antiserum to control A. baumannii infections.